The winner's curse: Evidence on the danger of aggressive credit growth in banking - Thomas Kick; Thilo Pausch; Benedikt Ruprecht (Deutsche Bundesbank, 2015)
Excessive credit creation by banks was at the root of the recent financial crisis. Nevertheless, micro-prudential regulation lacks a clear methodology to identify these banks. Combining arguments from banking and auction theory, we show that overoptimism causes excessive lending, subsequently yielding abnormal loan write-offs. We propose a new measure of excessive credit growth known from macroeconomics to identify credit booms and test our model for German bank and bankportfolio level data. Unlike traditional measures of (excessive) loan growth, our new measure identifies banks that are affected by abnormal loan write-offs, need capital support, or default in subsequent years.
Keywords: C23; G21; G32; 330; Excessive credit growth; Winner's curse; Loan-to-GDP gap; Micro-prudential regulation; Identifying weak banks